أثر استخـــدام تكنولوجيـا المعــلومات على كفـاءة الرقـابة الداخلية فـي معهـد النفط للتأهيــــل والتدريب- طرابلس (Comprehensive Journal of Science, 2025)
This research is designed to determine how information technology and the effectiveness of the internal control system are connected. The central research question it seeks to answer is:In what ways can information technology enhance how well the internal control system works? This is especially relevant considering how advanced and intricate management procedures have become, which makes keeping track of them challenging. The study's conceptual foundation drew from scholarly works and academic papers, which were used to highlight how information technology—the factor being examined—affects the efficiency of the internal control system—the result being measured.To gather information for the hands-on portion, questionnaires were given out to a selected set of accounting professionals and examiners. The information gathered was then analyzed through a descriptive and analytical process. The research showed these outcomes:-Utilizing information technology within the internal oversight framework is seen as a crucial approach to safeguard the Petroleum Institute's resources and holdings.-Fundamental concepts of information technology, communication, and internal control.- The use of information and communication technologyenhancesthe efficiency of internal control systems and risk awareness.The methodology employed was descriptive and analytical, gathering data from accounting and auditing staff through questionnaires. Statistical methods were then utilized to assess the data, highlighting the connection between employing accounting information technology and the effectiveness of internal controls. The focus of this research is on accountants and auditors working at the Petroleum Institute. It is recommended that they stay informed about new advancements in information technology, allocate funds to existing resources, encourage staff to pursue education and training to remain current, and ensure information security in protected areas.